Clinical Outcomes after Percutaneous Vertebroplasty for Pathologic Compression Fractures in Osteolytic Metastatic Spinal Disease - Lim, Bong-Suk; Chang, Ung-Kyu; Youn, Sang-Min (Journal of Korean Neurosurgical Society, 2009)
Percutaneous vertebroplasty (VP) can provide immediate stabilization in pathologic fractures of spinal tumors. However, long term follow-up data in cases of pathologic fractures are lacking. The authors report follow-up results of VP in 185 pathologic fractures of 102 spinal tumor patients. Percutaneous VP was performed at 185 vertebral bodies of 102 patients from 2001 to 2007. Retrospective analysis was done with medical records and radiological data. The change of visual analogue score (VAS), vertebral body (VB) height and kyphotic angle were measured preoperatively and on postoperative one day and at 3, 6, and 12 months. The patients were composed of metastatic spine tumors (81%) and multiple myeloma (19%). Involved spinal segments were between T6 and L5. Mean follow-up period was 12.2 months. VAS for back pain was 8.24 preoperatively, 3.59 (postoperative one day), 4.08 (three months) and 5.22 (one year). VB compression ratio changed from 21.33% preoperatively to 13.82% (postoperative one day), 14.36% (three month), and 16.04% (one year). Kyphotic angle changed from 15.35 degrees preoperatively to 12.03 degrees (postoperative one day), 13.64 degrees (three month), and 15.61 degrees (one year). Immediate pain relief was definite after VP in pathologic compression fracture of osteolytic spinal disease. Although VAS was slightly increased on one year follow-up, VP effect was maintained without significant change. These results indicate that VP could be a safe and effective procedure as a palliative treatment of the spinal tumor patients.